Access to Electricity in Afghanistan : A Review of Recent Data and Recommendations to Improve Utility Operations - World Bank (Washington, DC : World Bank, 2022)
It is generally believed that Afghanistan has one of the lowest levels of access to electricity in the world; the figure of 6 percent access on the national level is often cited. While it is certainly true that overall access to electricity is low in this overwhelmingly rural and poor country, a review of recent household survey data and updated national utility data suggests that the access to electricity is somewhat higher than has generally been supposed, particularly in urban Afghanistan. This note presents the new data and examines the implications of higher levels of access for policy makers and the managers of the power system in Afghanistan, particularly in Kabul. Recommendations to improve the quality of the utility's knowledge of the power system in Kabul follow the analysis of the survey data. The analysis of the Kabul Household Energy and Water Survey (KHEWS) data also considered the possibility that so-called 'minor consumers' might account for the discrepancy between the estimates of access to electricity more accurately reflect the actual level of access to electricity in Afghanistan and particularly in Kabul. At the very least, it would seem reasonable to conclude that the estimate based on Breshna data represents the minimum boundary of the estimate of access to electricity, while the survey data represent the maximum boundary, with the actual level somewhere in between and likely closer to the survey results.